Quantitative analysis of the puppet shapes in Ngayogyakarta Wayang Kulit. (2017) - Parikesit, Gea Oswah Fatah
In order to better understand and safeguard Wayang Kulit, the UNESCO-listed art of shadow theatre originated from Indonesia, a comprehensive research is necessary. In this paper we demonstrate that quantitative digital image analysis is very useful to investigate the puppet shapes in Ngayogyakarta Wayang Kulit. We found that various pairs of physical variables can be used to analyse the puppet shapes: the puppet level of details, the puppet surface area, the puppet perimeter length and the puppet height. Our results demonstrate that we can classify the different types of puppet characters using the puppet shapes. Moreover, we can also identify which ratio of variables is kept generally constant. Our method can be generally extended to other types of puppet theatres.